Co-occurrence of Wilson disease and Auto-Immune Hepatitis in 14-year-old female: A case report - Fadwa Ghassan Hameed; Inam Sameh Arif; Mohammed Mahmood Mohammed; Hala S. Arif (College of Pharmacy / Mustansiriyah University, 2022)
Unusual cases of coexistence between Wilson's disease and autoimmune hepatitis have occurred. There are characteristics of both diseases in this community of patients, and laboratory and histo pathological findings can be misleading. Wilson disease's clinical appearance can differ widely; thus, there is not always an easy diagnosis. In addition to being childhood and young adult illnesses, Wilson's disease can also be triggered at any age. Liver disease and cirrhosis, neuropsychiatric disorders, Kayser-Fleischer(KF.) rings, and acute hemolysis events are the primary characteristics of Wilson's disease, frequently in combination with acute liver failure. Diagnosis is extremely difficult for children and adults with active liver disease. None of the latest Wilson's disease laboratory tests are optimal and may not be specific. Therefore, by taking into account acute hepatitis similar to Wilson's disease and autoimmune hepatitis, concomitant treatment with immunosuppression and penicillamine may have a superior impact.